Atrophic jaw fracture and predictability in oral rehabilitation: case report - Miola Siqueira de Oliveira, João Pedro; Corso, Paola Fernanda Cotait de Lucas; de Oliveira, Gilson Cristiano; Scariot, Rafaela; Costa, Davani Latarullo (Brazilian Dental Science, 2020)
Introduction: The treatment of atrophic jaw fractures requires extensive knowledge by the maxillofacial surgeon. The correct diagnosis and planning optimize the possibility of oral rehabilitation towards many possible alternatives. The difficulty in repairing these fractures makes the treatment complex, in which normally invasive techniques are used. However; which give us satisfactory and predictable aesthetic-functional results. Objective: The objective of this work is to report an atrophic jaw fracture and posterior dental implants rehabilitation. Case report: A 53 years old female patient, victim of in face aggression referred to the emergency care. At the clinical examination, the patient had laceration in the upper lip region and the left side of the mandibular area, with bilateral mobility and paresis. In the oral examination, total lower and partial upper edentulism. After tomographic evaluation, a bilateral fracture of the mandibular body was confirmed, with significant bone fragments uneven. Surgery was performed with total transcervical access and use of reconstruction plate. After 90 days of follow-up, the oral rehabilitation with osseointegrated implants was performed. Conclusion: Complex atrophic mandible fractures in total edentulous patients can be treated with open reduction and stable fixation, allowing a faster return to normal function, improve of quality of life and assists in increasing safety for implant installation. Keywords Edentulous jaw; Jaw fixation techniques; Dental implants.